A Facile and Efficient Route for the Synthesis of Thiopyranoquinolines‐Fused Indole Moiety Using 2‐Chloroquinoline‐3‐carbaldehydes. Issue 40 (25th October 2019) - Moghaddam, Firouz Matloubi; Moafi, Atiyeh; Ziadkhani, Ainaz; Daneshfar, Maryam; Razaghdoost, Narges
Abstract: The reaction of 2‐chloroquinoline‐3‐carbaldehydes with indoline‐2‐thione in ethanol provides a series of novel indolo[3′, 2′:5, 6]thiopyrano[2, 3‐b]quinoline derivatives. The desired products were obtained in short reaction time and high yields (69‐93%) under mild reaction conditions. Abstract : A series of novel thiopyranoquinolines fused indole moiety with potential bioactivities by the reaction of 2‐chloroquinoline‐3‐carbaldehydes and thiooxindol were synthesized and a joint experimental–computational UV‐Vis spectra of the product was investigated. Mild reaction conditions, good functional‐group tolerance, relatively short reaction time, easy workup, using ethanol as a green solvent and high yield of products are the advantages of this protocol. All the structures of products were identified with spectroscopy methods.